Choriocapillaris thickness and density in axially elongated eyes - Panda-Jonas, Songhomitra; Holbach, Leonard; Jonas, Jost B. (Acta ophthalmologica, 2021)
Purpose Axial myopia is characterized by a thinning of the choroid. We examined whether the myopic choroidal thinning also includes a thinning of the choriocapillaris. Methods Using light microscopy, we measured thickness and density of the choriocapillaris at the posterior pole, posterior pole-equator midpoint (PPEMP), equator and close to the ora serrata on histological sections of 58 enucleated human globes (mean age: 62.4 ± 17.8 years; range: 24-88 years; mean axial length: 27.8 ± 4.0 mm; range: 22.0-37.0 mm). Results Choriocapillaris thickness decreased (p < 0.001) from the posterior pole (median: 3.9 µm; interquartile range (IQR): 3.3-6.0) to the equator (median: 2.7 µm; IQR: 1.5, 4.2). It was not significantly associated with axial length, neither at the posterior pole (p = 0.25), the PPEMP (p = 0.81), equator (p = 0.80) or ora serrata (p = 0.50). Mean choriocapillaris density decreased from the posterior pole to the equator (198 µm/300 µm; IQR: 152/300, 246/300 versus 156 µm/300 µm; IQR: 72/300, 216/300; p < 0.001). Choriocapillaris density was not significantly associated with axial length (posterior pole: p = 0.07; PPEMP: p = 0.33; equator: p = 0.22; ora serrata: p = 0.36). Conclusions The choriocapillaris thickness and density, decreasing from the posterior pole to the fundus periphery, were not significantly associated with axial length. These findings may be of interest for the understanding of high myopia and pathologic myopia.
Gesehen am 30.06.2021
First published: 19 June 2020